Conocimiento sobre puericultura y ablactación en mujeres hospitalizadas en el servicio de Gineco Obstetricia del Hospital Isidro Ayora - Valdivieso González, Franklin Santiago (2015)
Puericulture is about childcare since a pre-conceptional stage through adolescence. On the other hand, weaning refers to the introduction of complementary foods since 6 months without interrupting breastfeeding. This study focused on the knowledge about the care of newborns and how to make a proper weaning, therefore, it was proposed to establish the level of knowledge about childcare and weaning in women hospitalized in the service of gynecology and obstetrics of Isidro Ayora Hospital in the period 15 May - 15 June 2014. It was made a qualitative - quantitative, descriptive, transverse cut study of which 72 women participated, whom a survey focused on knowledge of newborn childcare and weaning was applied. This research showed that according to sociocultural characteristics, the participants reached a medium knowledge level about newborn childcare; whereas, regarding weaning, the participants gained low knowledge level. And, according to the parity of the participants, primiparous and multiparous they reached a medium knowledge level about newborn baby care; whereas, with regard to weaning, primiparous and multiparous they reached low knowledge level. It was concluded that, overall, 58.3 % of participants earned a medium knowledge level about newborn baby care; and 63.8 %, a low knowledge level about weaning. Keywords: Newborn, neonate, childcare, weaning, knowledge level.